Polyangiitis with Granulomatosis as a Paraneoplastic Syndrome of B-Cell Lymphoma of the Lacrimal Gland - Wills Sanín, Beatriz; Bolivar, Yenny R. Cárdenas; Carvajal, Jose J.; Quintero, Guillermo E.; Andrade, Rafael (Case Reports in Hematology, 2014)
Introduction. The clinical course of an autoimmune paraneoplastic syndrome parallels the natural history of the primary malignancy. In most cases, such paraneoplastic are syndromes hardly distinguishable from idiopathic autoimmune diseases. A case of polyangiitis with granulomatosis as a paraneoplastic syndrome in a patient with B-cell Lymphoma of the lacrimal gland has not yet been reported. Case Presentation. We present the case of a male patient with a B-cell Lymphoma of the lacrimal gland, who debuted with symptoms similar to rheumatoid arthritis and acute renal failure, secondary to polyangiitis with granulomatosis. The current pathophysiological hypotheses explaining the relationship between a lymphoproliferative disease and an autoimmune paraneoplastic disorder are discussed. Conclusion. Tumor-associated segmental necrotizing glomerulopathy is a very rare manifestation of glomerular diseases. Some atypical clinical features should increase the suspicion of an underlying tumor, in which case it is essential to treat the primary neoplasia, in order to control the autoimmune manifestations.